TRANSFORMASI TAJUSSALATIN DARI VERSI MELAYU KE DALAM VERSI JAWA: PERUBAHAN DALAM PENGUTIPAN AYAT-AYAT AL-QURAN: TRANSFORMATION OF TAJUSSALATIN FROM ITS MALAY VERSION INTO JAVANESE: CHANGES IN THE CITATION OF THE QURANIC VERSES - Kustri Sumiyardana (Penamas, 2014)
Hikayat Tajussalatin, a work by Bukhari al-Jawhari, is one popular text on Islamic politics. The text, which originated from the Malay tradition, was later translated into Javanese and given the title Serat Tajussalatin. Using reception theory, this article examines changes in the citation of the Quranic verses in the Javanese version of Tajussalatin compared to its Malay version. Javanese Serat Tajussalatin under study is a collection (number 53) of the Center for Historical and Traditional Values Studies (Balai Kajian Sejarah dan Nilai-nilai Tradisional) Yogyakarta, while its Malay version, Hikayat Tajussalatin, is available at the library of the Postgraduate Program of the Gadjah Mada University Yogyakarta. This study found that changes in the citation of the Quranic verses in Serat Tajussalatin include sound changes, and word and syllable addition. The author argues that these changes occurred because the writing of Serat Tajussalatin had to abide by the rules for writing Javanese traditional poetry. This transformation also indicates the way through which Javanese people adapted Islamic texts from other cultures. Key Words: Tajussalatin, Malay literature, Javanese literature, reception theory. Tajussalatin karya Bukhari al-Jauhari adalah salah satu teks populer tentang politik Islam yang berasal dari tradisi Melayu. Teks tersebut kemudian diterjemahkan dalam Bahasa Jawa dengan judul Serat Tajussalatin. Melalui teori resepsi, penelitian ini menjelaskan perubahan- perubahan pengutipan ayat-ayat Al-Quran dalam Tajussalatin versi Jawa, yang dibandingkan dengan Tajussalatin versi Melayu. Adapun sumber data Serat Tajussalatin adalah naskah koleksi Balai Kajian Sejarah dan Nilai-Nilai Tradisional Yogyakarta bernomor S53, sedangkan edisi teks Hikayat Tajussalatin tersedia di Perpustakaan Program Pascasarjana Universitas Gadjah Mada. Penelitian ini menemukan, bahwa perubahan yang terjadi pada pengutipan ayat Al-Quran dalam Serat Tajussalatin itu adalah perubahan bunyi, penambahan kata dan suku kata. Hal itu diakibatkan adanya aturan dalam puisi tradisional Jawa. Dengan demikian, transformasi ini menunjukkan cara orang Jawa Islam menerima teks-teks keislaman dari budaya lain (Melayu). Kata Kunci: Tajussalatin, sastra Melayu, sastra Jawa, Al-Quran, resepsi teks.